Implications, actors, and geopolitical levers of tourism. Israel / Palestine: what religious places tell us - Caroline Rozenholc-Escobar (Via@)
To contribute to the debates on the implications, actors and geopolitical levers of tourism, this article particularly examines religious tourism. For this reason, it is based on the first results of a research in urban geography on the role of the religious tourism industry in the realignment of the Israeli-Palestinian space and as a geopolitical lever for the positioning of Israel and of the Palestinian Territories on the international scene. It responds to this by looking at the places that contribute to producing this form of tourism; and the physical flows and symbolic movements of which these places are the objectives. On this territory where the touristic attraction continues despite the continuous violence, three types of sites have been identified: pilgrimage sites, alternative sites, and religious theme parks. This article will show how these sites, which will be collected under the term “places of mobility”, are linked and how they produce what we will refer to as “mobility of places”.